Er web- og tv-serien SKAM en serie om skam? - Christensen, Christa Lykke (Nordisk Tidsskrift for Informationsvidenskab og Kulturformidling, 2017)
In this article, I discuss whether the Norwegian teen web series drama SKAM (NRK, 2015-2017) is really about shame and to what extent the fictional characters of the series feel ashamed. The theoretical framework is based on a social psychological conceptualization of shame, supplemented by a micro-sociologically based analysis of the social meaning of face loss and shame. Shame may both entail a negative feeling and an active mechanism serving social and psychological purposes. The main characters of the series are used to analytically exemplify the role of shame and embarrassment. In conclusion, the series does thematize shame and the characters are often placed in conflicts that may give rise to shame. On the other hand, the series also suggests potential social strategies, to constructively avoid the face loss of shameful situations.